STEM Education Planning Based on Contextual Issues Sustainable Development Goals (SDGs) - Oktian Fajar Nugroho; Silvia Ratna Juwita; Nurul Febrianti (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
Integration and the practice of addressing real-world issues are crucial components of STEM education. In this study, which was conducted as part of an endeavor to boost students' and instructors' knowledge and interest in STEM education, existing STEM courses have been incorporated into the Indonesian curriculum requirements in order to address real-world problems. This article gives a description of the planning process for after-school STEM education programs, with a focus on significant global issues related to the Sustainable Development Goals (SDGs). At the junior high school level, the present curriculum requirements for all three STEM subjects will be integrated. Document analysis is the principal means of data collection. This consists of the standard papers of three distinct STEM fields, curriculum maps developed for schools, and documents pertaining to "Continuing Development Education." Four possible design problems are inspired by the Sustainable Development Goals (SDGs). These challenges blend standards selected from three distinct STEM domains and include several new interconnected concepts and skills. This description offers a way by which educators may be supported in the production of lessons or other equivalent STEM educational programs or activities by integrating curricular requirements with existing STEM disciplines for many levels and settings relevant to students.